Broadband Nonlinear Optical Response of Nitrogen-Doped Diamond - Xiao, Zhengguo; Fang, Yu; Song, Yinglin; She, Yanchao; Tian, Changhai; Zhang, Jie; Cui, Liqin; Li, Yong (Frontiers in Materials, 2021)
Nitrogen-doped diamond crystal with (111) orientation was synthesized with NaN3 additive in FeNi-C system at a pressure of 6.5 GPa and temperature 1310 °C conditions, employing the temperature gradient growth (TGG) method. Spectroscopic properties such as absorption spectrum and Raman spectrum as well as Fourier transform infrared (FTIR) spectrum were studied. FTIR spectroscopy of the C-N vibrational modes at 1344 cm-1 and 1130 cm-1 suggested a nitrogen content of 310 ppm. Its nonlinear optical (NLO) response was investigated by Z-scan technique under femtosecond regime. Due to the presence of nitrogen defects, the synthesized crystal performed large nonlinear absorption under both 800 nm and 532 nm wavelengths excitation. However, intrinsic diamond only experiences nonlinear refraction under these two wavelengths excitation. Its broadband NLO properties indicated that nitrogen-doped diamond crystals were suitable for the application of ultrafast optical devices.